Analysis of swimming speed and energy metabolism in competitive water polo games - Hohmann, A.; Frase, R. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
This study investigated the individual swimming profiles of 24 elite water polo players in a competitive situation i.e. during games at the 11th European Championships in Bonn, 1989. After an analysis of the individual maximum swimming speed (V ) and the speeds corresponding to the aerobic threshold of 2 mMm(~-2mM), the anaerobic threshold of 4 mM (V-4mM) and the limit of the super aerobic training zone of 6 mM (V-6mM), all movements of the players during the games were recorded using a time-lapse video recorder and evaluated by computer. The findings indicated that water polo necessitates an energy release which mainly results from high energy phosphates (ATP and CP) and aerobic metabolism.